Efektivitas Sanksi Pidana Dalam Sistem Perpajakan Di Indonesia: Tinjauan Terhadap UU Nomor 16 Tahun 2000 tentang Perubahan Kedua Atas UU Nomor 6 Tahun 1983 tentang Ketentuan Umum dan Tata Cara Perpajakan - Purwanto (Jurnal Risalah Hukum, 2006)
Tax is a source of national income which plays an important role in supporting the development in Indonesia. As one of the sources of the national income, tax serves two functions, that is budget function and managing function. In budget function context, tax is as a means of to provide as much fund as possible for the government treasury. In order to reach this function, we need to review the existence and effectiveness of crime sanction or imprisonment in the regulation of taxation, especially in article 38 as well as article 39 point (1) alphabetical b and f UU No. 16 Tahun 2000 tentang Perubahan Kedua Atas UU No. 6 Tahun 1983 tentang Ketentuan Umum dan Tata Cara Perpajakan. The crime sanction or the imprisonment is less effective to be applied because: (1) the crime sanction is contra productive towards the tax budget function. If the fine sanction is arranged and applied optimally in this regulation while the imprisonment is minimalized only to taxation crime, this effort will be more be effective to increase the national income from tax sector, and ( 2) the paradigm of the taxation policy is not in line with the policy on better investment made by the government, as well as with the economic development in general. Key Words : fungsi anggaran (budget fuction), pajak (tax), perpajakan (taxation), sanksi pidana (crime sanction)